2006
DOI: 10.1103/physrevb.73.161306
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for interfacial superconductivity in two-layer semiconducting heterostructures

Abstract: We have discovered superconductivity in the two-layer semiconducting monochalcogenide heterostrutures PbTe/ PbS, PbTe/ PbSe and PbTe/ YbS. By comparing data from two-layer samples with data from single monochalcogenide films we conclude that the superconductivity is connected with the interface between the two semiconductors. Evidence for the low dimensional nature of the superconducting interlayer is presented and a model that explains the appearance of single-interface superconductivity is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…In one early study of dislon theory [76], we have shown that the T c is determined by this competition effect: when the quantum effect is dominant, then T c is increased, and vice versa. The computed T c shows good agreement with a number of existing experimental data; particularly, it may provide a feasible explanation of the mysterious dislocation-induced superconductivity [75,119].…”
Section: Discussionsupporting
confidence: 77%
“…In one early study of dislon theory [76], we have shown that the T c is determined by this competition effect: when the quantum effect is dominant, then T c is increased, and vice versa. The computed T c shows good agreement with a number of existing experimental data; particularly, it may provide a feasible explanation of the mysterious dislocation-induced superconductivity [75,119].…”
Section: Discussionsupporting
confidence: 77%
“…Interface superconductivity between chalcogenides such as PbTe/PbSe and PbSe/PbS has also been reported 8 .…”
mentioning
confidence: 95%
“…The technique for the magnetotransport measurements is described in more detail elsewhere. [4][5][6] Experimental data and interpretation…”
Section: Techniques For Fabricating the Samples And For Making The Trmentioning
confidence: 99%
“…The period of this superconducting interface nanonetwork is 5.2 nm for PbTe/PbS nanostructures. [3][4][5][6] During a comprehensive experimental investigation it was found that two-layer PbTe/PbS heterostructures can be divided nominally into 3 categories (although there is no sharp boundary between these categories). 6 The first category includes samples with semiconducting layer thicknesses d !…”
Section: Techniques For Fabricating the Samples And For Making The Trmentioning
confidence: 99%